Insulin-like growth factor binding protein-3 inhibits cell adhesion via suppression of integrin β(4) expression - Lee, Hyo-Jong (Oncotarget, 2015)
We previously reported that IGF binding protein-3 (IGFBP-3), a major IGF-binding protein in human serum, regulates angiogenic activities of human head and neck squamous cell carcinoma (HNSCC) cells and human umbilical vein endothelial cells (HUVECs) through IGF-dependent and IGF-independent mechanisms. However, the role of IGFBP-3 in cell adhesion is largely unknown. We demonstrate here that IGFBP-3 inhibits the adhesion of HNSCC cells and HUVECs to the extracellular matrix (ECM). IGFBP-3 reduced transcription of a variety of integrins, especially integrin β(4), and suppressed phosphorylation of focal adhesion kinase (FAK) and Src in these cells through both IGF-dependent and IGF-independent pathways. IGFBP-3 was found to suppress the transcription of c-fos and c-jun and the activity of AP1 transcription factor. The regulatory effect of IGFBP-3 on integrin β(4) transcription was attenuated by blocking c-jun and c-fos gene expression via siRNA transfection. Taken together, our data show that IGFBP-3 has IGF-dependent and -independent inhibitory effects on intracellular adhesion signaling in HNSCC and HUVECs through its ability to block c-jun and c-fos transcription and thus AP-1-mediated integrin β(4) transcription. Collectively, our data suggest that IGFPB-3 may be an effective cancer therapeutic agent by blocking integrin-mediated adhesive activity of tumor and vascular endothelial cells.